Combustion stability and NOX emission characteristics of a 300 MWe tangentially fired boiler under ultra-low loads with deep-air staging. (15th April 2023) - Ma, Dafu; Zhang, Shouyu; He, Xiang; Zhang, Jian; Ding, Xian
Abstract: To accomplish the goals of carbon peaking and carbon neutrality in China, coal-fired units are required to implement real-time responses to the requirements of intermittent renewable energy sources. Thus, they typically operate under ultra-low loads, resulting in unstable combustion and high NOX emissions. In this study, the combustion stability and NOX emission characteristics of a 300 MWe tangentially fired boiler operated under ultra-low loads of 90 MWe and 60 MWe and with two pulverized coal (PC)-staging strategies at 90 MWe were investigated by performing experiments and numerical simulations. The results indicate that as the boiler load decreases to 60 MWe, the ignition of the PC flow is delayed and the imaginary circle gradually disappears. At 90 MWe, the shorter ignition distance, lower ignition heat, and higher furnace fullness degree during three-mill operation compared to those during two-mill operation suggest that the combustion is more stable with wider PC staging. As the load decreases from 90 MWe to 60 MWe during two-mill operation, the ignition distance and flame boundary temperature change negligibly and the ignition heat decreases, indicating stable combustion at 60 MWe in the case of easily ignitable coal. The upper burner exhibits greater combustion stability than the lower burner under ultra-low loads. Furthermore, the local mean stoichiometric ratio (LMSR) can be employed to predict corrected NOX concentrations at stable ultra-low loads. The vast majority of NOX is fuel NOX, and the average corrected NOX concentration at 90 MWe and 60 MWe is 795 mg/m 3 (O2  = 6%), which indicates that the deep-air-staging effect of the low-NOX combustion system is weakened, particularly when the LMSR is higher than 0.92. Highlights: Imaginary circles disappear at ultra-low loads especially at narrower PC-staging. Combustion stability with wider PC-staging is more ideal under ultra-low loads. Combustion is stable at 60MWe primarily because of the easily ignitable coal. The vast majority of NOX is fuel NOX and its quantity is great at ultra-low loads. Deep-air-staging function is weakened especially with higher LMSR.